End-of-life Decisions for Children in a Thai Pediatric Intensive Care Unit: A Qualitative Descriptive Study - Jongjai Jongaramraung (2020)
© 2020, Thailand Nursing and Midwifery Council. All rights reserved. The issue of healthcare decisions for terminally ill children is complex and presents a wide range of challenges and difficulties. This qualitative descriptive study was designed to investigate end-of-life decisions, based on health professionals’ perspectives, for children admitted to the pediatric intensive care unit. The participants comprised two physicians and 17 nurses, sampled purposively. Data collection was performed from November 2018 to June 2019, adopting in-depth interviews. Data analysis was carried out using the process proposed by Creswell. The main findings revealed that parents ultimately took responsibility for end-of-life decisions related to their terminally ill child. There were four main categories describing end-of-life decisions for a terminally ill child: Making definite end-of-life diagnosis; Communicating to assure parental understanding; Allowing parents to choose end-of-life options; and Initiating end-of-life care. The findings of this study provide an insight into parental decision for their terminally ill child during this critical stage. Such essential knowledge is useful as a foundation to improve end-of-life decisions in the pediatric intensive care unit, practically and effectively for nurses and other health professionals.